The Use of Audit to Identify Maternal Mortality in Different Settings: Is It Just a Difference Between the Rich and the Poor? - Jeroen van Dillen, Jelle Stekelenburg, Joke Schutte, Gijs Walraven and Jos van Roosmalen (World Health & Population, 2007)
Objective: To illustrate how maternal mortality audit identifies different causes of and contributing factors to maternal deaths in different settings in low- and high-income countries and how this can lead to local solutions in reducing maternal deaths. Design: Descriptive study of maternal mortality from different settings and review of data on the history of reducing maternal mortality in what are now high-income countries. Settings: Kalabo district in Zambia, Farafenni division in The Gambia, Onandjokwe district in Namibia, and the Netherlands. Population: Population of rural areas in Zambia and The Gambia, peri-urban population in Namibia and nationwide data from the Netherlands. Methods: Data from facility-based maternal mortality audits from three African hospitals and data from the latest confidential enquiry in the Netherlands. Main Outcome Measures: Maternal mortality ratio (MMR), causes (direct and indirect) and characteristics. Results: MMR ranged from 10 per 100,000 (the Netherlands) to 1,540 per 100,000 (The Gambia). Differences in causes of deaths were characterized by HIV/AIDS in Namibia, sepsis and HIV/AIDS in Zambia, (pre-)eclampsia in the Netherlands and obstructed labour in The Gambia. Conclusion: Differences in maternal mortality are more than just differences between the rich and poor. Acknowledging the magnitude of maternal mortality and harnessing a strong political will to tackle the issues are important factors. However, there is no single, general solution to reduce maternal mortality, and identification of problems needs to be promoted through audit, both national and local.